Corporate Branding in Online Startups - Fojtíková, Pavlína; Karlíček, Miroslav, 1979-; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The purpose of this Master's thesis is to explore corporate branding in online startups from the entrepreneurial perspective. In total, nine companies -- mostly Czech and German-based Internet startups - were researched. The principal method employed is the qualitative research based on in-depth interviews with startup founders and managers. The thesis shows that the literature on corporate branding mostly coincides with the reality of online startups, reveals that there is no consensus about the importance of corporate branding among startup representatives and explains the corporate brand building practices in online startups. In conclusion, recommendations for prospective entrepreneurs are proposed.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses